The Turun Mani Tradition in Gayo: an Analysis of Hadith on Aqiqah in Central Aceh - Al-Farabi Melala; Abdul Halim (JURNAL AT-TURAS, 2024)
This study explores the integration of local traditions within Islam through an examination of the Turun Mani tradition among the Gayo community in Central Aceh. This tradition represents a unique implementation of the Aqiqah ritual, incorporating local cultural elements and reflecting harmony between Islamic teachings and local customs. The research aims to examine the practice of the Turun Mani tradition, understand the Gayo community's perception of hadiths related to Aqiqah, and analyze the quality of the referenced hadiths. Employing a qualitative method with a living hadith approach, this study involves in-depth interviews with selected informants, including religious leaders, cultural figures, and practitioners of the tradition, as well as literature reviews of hadiths and primary texts. The findings reveal that the Turun Mani tradition adapts local cultural elements—such as the Begenap ritual, bathing the newborn with coconut water and kaffir lime, and protective prayers—while preserving the essence of Aqiqah. The Gayo community’s understanding of the hadiths underlying this tradition is largely inherited and lacks critical examination of the hadiths' authenticity. The Turun Mani tradition not only reinforces local wisdom but also supports the primary objectives of Maqāṣid al-Syarī‘ah, such as protecting faith, life, lineage, and intellect. Despite challenges posed by modernization, the tradition endures as a manifestation of harmony between religion and culture. This research contributes to the study of living hadith and the relationship between Islam and local traditions in Indonesia.